A standardised model for stool banking for faecal microbiota transplantation: a consensus report from a multidisciplinary UEG working group. Issue 2 (9th March 2021) - Keller, Josbert J.; Ooijevaar, Rogier E.; Hvas, Christian L.; Terveer, Elisabeth M.; Lieberknecht, Simone C.; Högenauer, Christoph; Arkkila, Perttu; Sokol, Harry; Gridnyev, Oleksiy; Mégraud, Francis; Kump, Patrizia K.; Nakov, Radislav; et al.
Abstract: Background: Faecal microbiota transplantation is an emerging therapeutic option, particularly for the treatment of recurrent Clostridioides difficile infection. Stool banks that organise recruitment and screening of faeces donors are being embedded within the regulatory frameworks described in the European Union Tissue and Cells Directive and the technical guide to the quality and safety of tissue and cells for human application, published by the European Council. Objective: Several European and international consensus statements concerning faecal microbiota transplantation have been issued. While these documents provide overall guidance, we aim to provide a detailed description of all processes that relate to the collection, handling and clinical application of human donor stool in this document. Methods: Collaborative subgroups of experts on stool banking drafted concepts for all domains pertaining to stool banking. During a working group meeting in the United European Gastroenterology Week 2019 in Barcelona, these concepts were discussed and finalised to be included in our overall guidance document about faecal microbiota transplantation. Results: A guidance document for all domains pertaining to stool banking was created. This document includes standard operating manuals for several processes involved with stool banking, such as handling of donor material, storage and donor screening. Conclusion: The implementation of faecal microbiota transplantation by stool banks in concordance with our guidance document will enable quality assurance and guarantee the availability of donor faeces preparations for patients.